Ethernet-based C-RAN fronthaul - Marques, Pedro Miguel Costa (2018)
For the last decade mobile data traffic has been increasing at impressive rates. The proliferation of mobile devices together with high-bandwidth services like video and music streaming, social media and other cloud services have increased the load on top of the mobile network infrastructure. In order to support this massive increase in both users and bandwidth the next generation of mobile telecommunications network - 5G - explores new approaches, like the utilization of new frequency bands and the densification of base stations. This kind of requirements along with the inefficiency of the co-location of base band processing near the radio units encourages a rethink of traditional radio access networks. In this scenario emerges the C-RAN paradigm that intend to centralize all the base band processing (BBU) and replace current base stations for simpler, more efficient and compact solutions that only incorporate the radio front-end and respective radio processing (RRH). In addition to these benefits, centralized processing facilitates virtualization and resource sharing, interference management and cooperative processing technologies. This split of functions brings however, some challenges in respect to the data rates, bandwidth and latency in the link that connects BBUs and RRHs - the fronthaul. Today’s existing standards like CPRI weren’t originally designed for such applications and present some intrinsic bandwidth and flexibility limitations. It’s considered that another approach, based on packet switching, could mitigate some of these problems in addition to bring some advantages such as statistical multiplexing, flexible routing and compatibility with current widespread packet switching networks. They do however, present a number of challenges regarding latency and synchronization. This dissertation work focuses on the study and development of a fronthaul solution based in 10 Gigabit Ethernet over optical fiber. Development is done on top of two development kits based in Field Programmable Gate Array (FPGA) and implemented in an already operational C-RAN test-bed - currently with CPRI based fronthaul - at the Instituto de Telecomunicações - Aveiro.